Processing and mechanical properties of hot-pressed zirconium diboride – zirconium carbide ceramics. Issue 11 (September 2022) - Neuman, Eric W.; Fahrenholtz, William G.; Hilmas, Gregory E.
Abstract: ZrB2 was mixed with 0.5 wt% carbon and up to 10 vol% ZrC and densified by hot-pressing at 2000 °C. All compositions were > 99.8% dense following hot-pressing. The dense ceramics contained 1–1.5 vol% less ZrC than the nominal ZrC addition and had between 0.5 and 1 vol% residual carbon. Grain sizes for the ZrB2 phase decreased from 10.1 µm for 2.5 vol% ZrC to 4.2 µm for 10 vol% ZrC, while the ZrC cluster size increased from 1.3 µm to 2.2 µm over the same composition range. Elastic modulus was 505 GPa and toughness was 2.6 MPa·m ½ for all compositions. Vickers hardness increased from 14.1 to 15.3 GPa as ZrC increased from 2.5 to 10 vol%. Flexure strength increased from 395 MPa for 2.5 vol% ZrC to 615 MPa for 10 vol% ZrC. Griffith-type analysis suggests ZrB2 grain pullout from machining as the strength limiting flaw for all compositions.